2019
DOI: 10.1136/emermed-2018-207563
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of non-invasive ventilation in ‘very old’ patients with acute respiratory failure: a retrospective study

Abstract: BackgroundNon-invasive ventilation (NIV) is increasingly used to support very old (aged ≥85 years) patients with acute respiratory failure (ARF). This retrospective observational study evaluated the impact of NIV on the prognosis of very old patients who have been admitted to the intermediate care unit (IMC) of the Emergency Department of the University Hospital Policlinico-Vittorio Emanuele of Catania for ARF.MethodsAll patients admitted to the IMC between January and December 2015 who received NIV as the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This led the authors to recommend caution when considering NIRS in very old patients. In contrast, a subsequent retrospective, observational study on patients undergoing NIRS to treat ARF of various aetiologies (i.e., COPD exacerbation, acute pulmonary oedema, sepsis, and pneumonia) [ 28 ] showed that the in-hospital mortality rate of very old individuals (≥85 years) was comparable to that observed in younger patients, despite a higher predicted mortality in the former population. We believe that these contrasting observations may be attributable to the fact that NIRS outcomes in old age patients can be heavily influenced by the baseline disease, with hypoxemic ARF being the least responsive to treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This led the authors to recommend caution when considering NIRS in very old patients. In contrast, a subsequent retrospective, observational study on patients undergoing NIRS to treat ARF of various aetiologies (i.e., COPD exacerbation, acute pulmonary oedema, sepsis, and pneumonia) [ 28 ] showed that the in-hospital mortality rate of very old individuals (≥85 years) was comparable to that observed in younger patients, despite a higher predicted mortality in the former population. We believe that these contrasting observations may be attributable to the fact that NIRS outcomes in old age patients can be heavily influenced by the baseline disease, with hypoxemic ARF being the least responsive to treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency departments are receiving a growing up number of elderly patients with acute respiratory failure (ARF). 1 As the prevalence of chronic respiratory and cardiovascular diseases increases with age 2 , it is common that elderly patients often present to the emergency department (ED) for an exacerbation of their chronic pathologies manifested by an ARF in most serious cases. 1,2 The therapeutic approach with ARF must be critical elderly.…”
Section: Introductionmentioning
confidence: 99%
“…1 As the prevalence of chronic respiratory and cardiovascular diseases increases with age 2 , it is common that elderly patients often present to the emergency department (ED) for an exacerbation of their chronic pathologies manifested by an ARF in most serious cases. 1,2 The therapeutic approach with ARF must be critical elderly. 2,5 According to the literature and current guidelines, NIV represents a first choice ventilatory technique to be considered in the management of some diseases which have a high prevalence in the elderly and this concerns particularly acute heart failure (AHF) and acute exacerbation of chronic obstructive pulmonary diseases (AECOPD) for which NIV has widely established effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation